Influence of YouTube Referencing on the Academic Performance among Senior High School Students in South Ubian, Tawi-Tawi - Abdulnasil, Adzma (International Journal of Sustainability and Advanced Integrated Research, 2026)
This study examined the relationship between YouTube referencing and the academic performance of senior high school students in South Ubian, Tawi-Tawi during the School Year 2025–2026. Anchored on the Cognitive Theory of Multimedia Learning, Social Learning Theory, and Constructivist Learning Theory, the study investigated students’ frequency of YouTube use, perceptions of YouTube as a learning reference, and their academic performance. A quantitative descriptive research design was employed involving 290 senior high school students selected through random sampling from three senior high schools in South Ubian, Tawi-Tawi. Data were collected using a validated self-constructed questionnaire-checklist utilizing a Likert Scale. Statistical tools such as frequency, percentage, weighted mean, standard deviation, Kruskal-Wallis H Test, and Mann-Whitney U Test were used in the analysis. Findings revealed that students moderately used YouTube as a supplementary learning reference, particularly for subject tutorials, project preparation, and academic support. Students generally perceived YouTube as a useful and effective educational tool that enhanced engagement, understanding, motivation, and access to academic information. Significant relationships were identified between students’ frequency of YouTube use and academic performance, as well as between students’ perceptions of YouTube and academic performance. The study further found significant differences in academic performance based on age and gender, while no significant differences were observed in terms of grade level and time span of YouTube use. Overall, the study concluded that YouTube positively influenced students’ academic performance when used responsibly as a supplementary learning resource. The study recommended the responsible use of YouTube, integration of educational video content into instruction, and guidance in selecting reliable online materials. The study supports Sustainable Development Goal (SDG) 4 on Quality Education by highlighting the role of digital learning platforms in promoting accessible and flexible learning opportunities. It also relates to SDG 9 on Industry, Innovation and Infrastructure through the integration of digital technology in education. In terms of sustainability impact, the study contributes to educational and technological sustainability by encouraging the responsible use of digital learning resources to enhance student learning outcomes, particularly in geographically isolated communities such as South Ubian, Tawi-Tawi.